PENGARUH KNOWLEDGE SHARING TERHADAP KINERJA PUSTAKAWAN DI DINAS KEARSIPAN DAN PERPUSTAKAAN PROVINSI SUMATERA BARAT - Tiara, Anna; Elva Rahmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effect of knowledge sharing on librarians’ performance at the Provincial Archives and Library Office of West Sumatra. The background of this research arises from the low effectiveness of collaboration among librarians, particularly the lack of systematic knowledge transfer between senior and junior staff, which affects service quality and performance. A quantitative descriptive approach was employed with a population of 30 librarians, all of whom were taken as the sample. Data were collected through questionnaires using a Likert scale, observations, interviews, and documentation, and analyzed using simple linear regression with SPSS version 23. The results show that knowledge sharing among librarians is categorized as very good, with an average score of 3.86, while librarians’ performance is also categorized as very good, with an average score of 3.80. The regression analysis indicates that Fcount (7.278) is higher than Ftable (4.080) with a significance value of 0.010 (<0.05), confirming that knowledge sharing has a significant and positive influence on librarians’ performance. The coefficient of determination (R²) shows that knowledge sharing contributes 13.1% to performance improvement, while the remaining 86.9% is influenced by other factors not examined in this study.